Aminoluciferin 4-hydroxyphenyl amide enables bioluminescence detection of endogenous tyrosinase. Issue 47 (23rd November 2018) - Tang, Chunchao; Jin, Lei; Lin, Yuxing; Su, Jing; Sun, Yingai; Liu, Pan; Li, Qi; Wang, Guankai; Zhang, Zheng; Du, Lupei; Li, Minyong
Abstract : We report a new BL probe, TyrBP-3, which not only exhibits high sensitivity and selectivity for imaging tyrosinase in vitro, and good cell-permeability for detecting tyrosinase in living cells, but can also visualize the level of tyrosinase activity in tumors of living animals. Abstract : Tyrosinase, a copper-containing enzyme existing widely in plants, animals and microorganisms, usually serves as an important biomarker in melanoma, and is also related to hyperpigmentation of the skin, melasma, age spots and albinism. At present, only one bioluminescent probe has been applied to image tyrosinase in cells. Thus, it's of great significance to develop a new bioluminescent probe that can detect tyrosinase in living cells and in live animals. In the current work, we report a new BL probe, TyrBP-3, which not detect tyrosinase in vitro and in living cells, but can also visualize the level of tyrosinase activity in tumors of living animals. In summary, TyrBP-3 is the first bioluminescent probe that can image tyrosinase on a cellular level. Hence, we anticipate that TyrBP-3 can be a good tool to monitor tyrosinase in complex biosystems in the future.